Polite Language in the Teachings of Gus Baha According to the Qur’an: Analysis and Practical Implications - Santoso, Dwi (Journal Corner of Education, Linguistics, and Literature, 2025)
This article explores how renowned Islamic preacher Gus Baha promotes the use of polite language by drawing on timeless Qur’anic guidance. Using a qualitative approach that combines an extensive literature review with content analysis, we examine ten specific examples from his teachings and compare them with key Qur’anic principles. Our analysis reveals that practices such as warm greetings, respectful titles, gentle word choices, and constructive feedback not only mirror the ethical values embedded in the Qur’an but also serve as practical strategies for building stronger, more caring communities. Furthermore, the study discusses how these traditional ethical frameworks can address modern communication challenges, particularly in our fast-paced and diverse digital world. By emphasizing respectful dialogue and empathetic interaction, the findings suggest that the deliberate use of polite language can significantly enhance interpersonal relationships and foster greater social harmony. Ultimately, this research provides practical insights into how the thoughtful application of respectful language, as advocated by Gus Baha, can contribute to a more inclusive and interconnected society.